Principal Component Analysis of the Social and Behavioral Rhythms Scale in elderly - Giulia Cossu; Mirian Agus; Laura Atzori; Cesar Ivan Aviles Gonzales; Luigi Minerba; Caterina Ferreli; Roberto Puxeddu; Germano Orrù; Alessandra Scano; Ferdinando Romano; Elisa Pintus; Maria Petronilla Penna; et al. (SAGE Publishing, 2021)
Background: Changes in social and behavioral rhythms (SBR) in elderly are related to health status. Nevertheless, there is no data on factor analysis of the Brief Social Rhythm Scale (BSRS) an internationally well-known tool in this field. The aim was to analyze, in elderly, the factorial structure of the Italian version of BSRS. Design and Methods: Principal Component Analysis of the BSRS carried out in elderly living at home. Results: Sample of 141 participants (83 Females, 58,9%), aged 72.3±4.8. All the items of the questionnaire were related and could compose a single factor, explaining 56% of variance. A solution adopting two factors, the first (including items 1,2,3,4,9,10), the second (including items 5,6,7,8), covered cumulatively 78.8% of the variance. Conclusion: The study confirms that the BSRS is consistent with the idea for which it was built and can be useful for the study of regularity of SBR in old adults.